Physical Activity Increases White Matter Microstructure in Children - Chaddock-Heyman, Laura; Erickson, Kirk I.; Kienzler, Caitlin; Drollette, Eric S.; Raine, Lauren B.; Kao, Shih-Chun; Bensken, Jeanine; Weisshappel, Robert; Castelli, Darla M.; Hillman, Charles H.; Kramer, Arthur F. (Frontiers in Neuroscience, 2018)
Children are becoming increasingly inactive, unfit, and overweight, yet there is relatively little causal evidence regarding the effects of physical activity on brain health during childhood. The present study examined the effects of an after-school physical activity program (FITKids2) on the microstructure of white matter tracts in 7- to 9-year-old children. We measured the microstructural properties of white matter via diffusion tensor imaging in one hundred and forty-three children before and after random assignment to either a 9-month after-school physical activity program (N=76, mean age = 8.7 years) or a wait list control group (N=67, mean age = 8.7 years). Our results demonstrate that children who participated in the physical activity program showed increased white matter microstructure in the genu of the corpus callosum, with no changes in white matter microstructure in the wait list control group which reflects typical development. Specifically, children in the physical activity program showed increases in fractional anisotropy (FA) and decreases in radial diffusivity (RD) in the genu from pre- to post-test, thereby suggesting more tightly bundled and structurally compact fibers (FA) and increased myelination (RD), with no changes in estimates of axonal fiber diameter (axial diffusivity, AD). The corpus callosum integrates cognitive, motor, and sensory information between the left and right hemispheres of the brain, and the white matter tract plays a role in cognition and behavior. Our findings reinforce the importance of physical activity for brain health during child development.